DHEA and polycystic ovarian syndrome: Meta-analysis of case-control studies. - Jiby Jolly Benjamin; MaheshKumar K; Teena Koshy; Maruthy K N; Padmavathi R (PLoS ONE)
Background Polycystic ovarian syndrome is a heterogenous endocrine disorder characterized by irregular menstrual cycles, hirsuitism and polycystic ovaries. It is further complicated by metabolic syndrome, infertility and psychological stress. Although the etiopathogenesis is unclear, many studies have pointed out the role of stress in this syndrome. DHEA, being a stress marker is being used by scientists to compare the stress levels between polycystic ovarian cases and healthy controls. However, the results obtained from previous studies are equivocal. Objective To perform meta-analysis and find the association between stress and the syndrome. Data sources Relevant data till January 2021 were retrieved from PubMed, Scopus, Embase and Web of Science using MeSH terms. Study selection Case-control studies having PCOS subjects as cases and healthy women as controls were selected provided; their basal DHEA levels were mentioned in the published articles. Data extraction Two authors independently extracted the articles and qualified the final studies. Data synthesi Pooled meta-analysis was done using random effect model and showed level of DHEA statistically significant in PCOS compared to healthy controls (SMD = 1.15, 95% CI = 0.59-1.71).Heterogeneity was statistically significant as well (I2 = 95%). Conclusion Thismeta-analysis on DHEA and PCOS has helped in generating evidence regarding the involvement of stress in the pathogenesis of PCOS.